An empirical study of corporate social responsibility disclosure: evidence from China - Lin, Jiachi (2019)
In today's society, the issue of corporate social responsibility(CSR) is highly concerned by the public. The implementation of CSR is in line with the goal of sustainable development globally. Over the past decades, there appeared substantial studies in relation to CSR, but most studies were conducted in developed countries, with less subject to developing countries( Waris, 2017; Fifka, 2013). Therefore, this paper takes the largest developing country China as the object of research. The purpose of this paper is to identify the extent and content of CSR information disclosed in China, and the determinants that drive corporates to make CSR disclosure. Content analysis is introduced in this paper and it is used to measure the level of CSR disclosure, along with the measurement framework established. The included items and categories for evaluation of CSR refer to the study of Manuel & Lucia(2008). Four explanatory variables are examined in this paper, which are firm size(SIZE), industry type(IND), government ownership(GOV) and ownership concentration(CON). Profitability(ROE) and leverage(LEV) are adopted as control variables in the paper. The regression results indicate that SIZE and IND are significantly positively correlated with CSR disclsoure, while GOV and CON do not show significant relationship with CSR disclosure. Stakeholder theory and legitimacy theory are relevant in explaining these findings. Finally, the findings of this paper could provide reference for those government policy-makers and company managers.